A comparative analysis of two cross-sectional surveys of healthcare workers' hand hygiene knowledge, intentions, access and product preferences between two university hospitals, one in Norway and one in Canada - Mediå, Anne Kristine (Universitetet i Tromsø, 2008)
Objective: Vancouver General Hospital (VGH) and The University Hospital of Northern Norway in Tromsø (UNN-Tromsø) were compared for self-reported differences in level of knowledge and intentions to comply with the hand hygiene guidelines. Hand hygiene products were also assessed for preference of use, access, gentleness and promotion of hand hygiene compliance. Methods: A cross-sectional quality assurance staff survey was made available at UNN- Tromsø and at VGH in both print and in electronic format. Results: A total of 1230 of the 10,000 full time health care workers (HCWs) (12%) responded to the survey. UNN-Tromsø HCWs were less satisfied with the gentleness of soap and water than were VGH HCWs. UNN-Tromsø HCWs reported greater access to both soap and water and hand rub than was reported by HCWs at VGH. Promoting compliance was influenced by access for both VGH and UNN- Tromsø whereas, gentleness promoted compliance only for Tromsø-UNN HCWs. The HCWs at VGH had higher mean scores on intention to comply with hand hygiene guidelines. Conclusion: Environmental factors such as gentleness to the hand and easy accessibility of hand cleansers were associated with compliance to the hand hygiene guidelines. Further, knowledge of hand hygiene guidelines was positively associated with compliance.